A Guide to Successful Consulting - Stryker, Steven C. (Government Institutes, 2011)
Many consultants are forced to learn the basic principles and techniques of consulting on the job. Even though this lack of preparation can lead to several problems that could be avoided, there are few practical resources available to guide the new consulting professional to an understanding of what is required for a successful consulting practice. In A Guide to Successful Consulting, author Steven C. Stryker presents an essential introduction to the fundamental concepts and tools of the successful consultant. This book describes, through a comprehensive approach that unites theory and practice, consulting principles for all those wishing to expand their abilities to initiate and implement organizational change. It lays the groundwork for the perceptive handling of each assignment through the integration of knowledge, experience, and instinct. It thoroughly examines the major aspects of a consulting assignment, along with the required practical skills and techniques. Explanatory graphics and case studies based on real-world examples abound to ensure that ideas can become roadmaps to developing important consulting tools. Take-away checklists and tables of useful information provide a practical way for consultants to review and apply the necessary knowledge for successful practice. This book enables aspiring consulting professionals to have a better grasp of the environment and challenges of the practice of professional consulting today.